1989
DOI: 10.1149/1.2097095
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Etching in CrO3 ‐  HF  Solutions: I . High Ratios

Abstract: The dissolution of silicon in aqueous CrO3‐HF solutions was investigated by etching and electrochemical measurements. At high false[HFfalse]/false[CrO3false] ratios, etching occurs via an electroless process in which reduction of Cr (VI) and oxidation of Si take place simultaneously. A model is presented for the anodic dissolution of silicon in HF solutions. The electrochemical results have been used to determine the relevant rate constants for the different reaction steps. Combining cathodic and anodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A similar effect has been observed with silicon in HF solutions containing other oxidizing agents. 18,[20][21][22] Electrons from intermediates of the etching process can be thermally excited to the conduction band. Under depletion conditions, the electrons are driven from the surface, and registered as an anodic current.…”
Section: Resultsmentioning
confidence: 99%
“…A similar effect has been observed with silicon in HF solutions containing other oxidizing agents. 18,[20][21][22] Electrons from intermediates of the etching process can be thermally excited to the conduction band. Under depletion conditions, the electrons are driven from the surface, and registered as an anodic current.…”
Section: Resultsmentioning
confidence: 99%
“…For electroless etching of Si in CrO 3 /HF solutions a C F exponent of 1.5 has also been observed for the anodic partial current. 11 Hassan et al 10 made an extensive rotating disk electrode study of the process at p-Si in different solutions at different pH values. They observed that the dissolution process was under mixed kinetic/ diffusion control and analyzed their results according to the Koutecky-Levich equation, to separate the measured currents into a kinetic and a diffusional part.…”
mentioning
confidence: 99%
“…As in the case of anodic etching, the oxidation of silicon also involves hydrogen evolution. A recent study [12] showed that for a 6 M HNO , 6M HF etchant, the stoichiometry of the oxidation reaction is given by (4) Other oxidizing agents such as IrCl , MnO , and CrO can inject holes into the valence band of silicon and, hence, can be considered for electroless etching [13], [65], [66]. Such systems are, however, not as widely used.…”
Section: A Acidic Fluoride Solutionsmentioning
confidence: 99%
“…It is also possible to use oxidizing agents which inject holes directly into the valence band of silicon. Examples are HNO or CrO at low pH [10], [62]- [64], [13], [65], [66] and Fe(CN) or MnO at high pH [16], [67], [68], [20]. Such systems do not discriminate between uncontacted silicon and silicon in Ohmic contact with a metal.…”
Section: Choice Of Oxidizing Agentsmentioning
confidence: 99%